1982
DOI: 10.1136/gut.23.4.292
|View full text |Cite
|
Sign up to set email alerts
|

Gastric emptying of solids in man.

Abstract: SUMMARY The influence of the type and size of solid particles on their emptying from the stomach was studied using isotopically labelled chicken liver and inert particles in normal subjects and in patients who had undergone gastric surgery. In normal subjects, initial emptying of the liver was slower than that of inert particles both for large liver cubes (1 cm) and small cubes (0.3 cm). Liver emptying subsequently accelerated to be faster than emptying of the inert particles. Overall emptying of the liver giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

1984
1984
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(42 citation statements)
references
References 15 publications
1
40
0
1
Order By: Relevance
“…The present study was to clarify the affect of the diameters of indigestible solids in humans. It was reported in humans that in the fed state the pyloric sphincter is contracted and only small indigestible solids (less than 5.0 mm) are able to empty as "fortuitous emptying" with the meal, but large objects are not emptied in such a manner (Holt et al, 1982). It was also reported that the emptying of indigestible solids depends largely on the composition of the meal (Ewe et al, 1991) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study was to clarify the affect of the diameters of indigestible solids in humans. It was reported in humans that in the fed state the pyloric sphincter is contracted and only small indigestible solids (less than 5.0 mm) are able to empty as "fortuitous emptying" with the meal, but large objects are not emptied in such a manner (Holt et al, 1982). It was also reported that the emptying of indigestible solids depends largely on the composition of the meal (Ewe et al, 1991) .…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that the gastric emptyings of liquids, digestible solids, and indigestible solids do not take place at the same rate (Holt et al, 1982Mojaverian et al, 1985.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major factor influencing the gastric emptying of oral dosage forms is whether they are administered with or without food. 12 In the fasted state, drug preparations are retained in the stomach until they are removed by the phase III contractions of the migrating myoelectric complex (MMC). Phase III of the MMC is known as the ''housekeeper wave'' and acts to empty the stomach of swallowed saliva, cellular debris, and indigestible solids.…”
Section: Gastrointestinal Transitmentioning
confidence: 99%
“…La fonction de l'antre est en fait d'exprimer les suspensions de fines particules susceptibles d'évacuation à l'instar des liquides (Hinder et Kelly, 1980) et de retenir et triturer les solides pour en assurer la liquéfaction (Meyer et al, 1979 ;Meyer, 1980). Ce rôle de filtre sélectif est vérifié chez le porc (Clémens et al, 1975) comme chez l'Homme (Malagelada, 1977 ;Holt et al, 1982). Mais (Laplace, 1982 (Nagaoka, 1968 ;Kelly et Code, 1969 ;Wilbur et Kelly, 1973 ;Stoddard et al, 1973 ;Bone et al, 1977a) ; défaut de coordination des activités antrales et duodénales (Stoddard et Duthie, 1976).…”
Section: Introductionunclassified